Decrease in cross-border tobacco purchases despite intensification of antitobacco policies in France. Issue 4 (3rd August 2020) - Gomajee, Ramchandar; Torregrossa, Hugo; Bolze, Camille; Melchior, Maria; El-Khoury Lesueur, Fabienne
Abstract : Background: Recently, France has intensified tobacco control policies which included gradual increase in tobacco product price and the introduction of plain packaging. However, there has been suggestion that cross-border tobacco purchases from neighbouring countries, with lower tobacco prices, will increase. We examine trends in cross-border tobacco purchases among smokers concurrent with the implementation of tobacco control measures between 2016 and 2017. Methods: Description des Perceptions, Images, et Comportements liés au Tabagisme is a two-wave cross-sectional national telephone survey of French adults aged 18–64 years, which recruited a total of 2167 smokers (2016: n=1238; 2017: n=929). Data were weighted to be representative of the French adult population. The association between study wave and cross-country tobacco purchases was examined across study waves using a multivariable logistic regression model (adjusted ORs: ORa (95% CI)). Results: Less than half (38.5%) of smokers declared cross-border tobacco purchases in the last year, which were mostly done on occasional basis: 22.6% purchased tobacco cross-border once or twice yearly. In 2017, as compared with 2016, cross-border tobacco purchases by French smokers decreased (ORa =0.81, 95% CI 0.68 to 0.98). Other factors associated with cross-border tobacco purchases included sex, and driving distance to a border. Conclusion: In France, the increase in tobacco product price and the introduction of plain packaging did not contribute to increasing rates of out-of-country purchases of tobacco products, probably due to the overall decrease in smoking levels. However, a harmonisation of tobacco product prices and plain packaging policies across Europe might further improve tobacco control throughout the continent.